Mucinous adenocarcinoma transformed from tailgut cyst: a case report and review of the literature - Guo, Qianyu; Parker, Joseph B.; Henderson, Adam; Khoor, Andras; Mohseni, Michael M. (Frontiers in Oncology, 2026)
Tailgut cysts often present asymptomatically or with nonspecific symptoms. While commonly benign, they may in rare cases be malignant, often transforming into adenocarcinoma. We present a 68-year-old female who presented with a sacral mass and abscess. Upon Emergency Department presentation, her inflammatory markers were elevated as well as her lactate. Initially, the patient was treated for possible infectious etiology with parenteral antibiotics. However, an MRI was obtained that showed concerns for myxoid neoplasm or chordoma. A biopsy was subsequently performed that revealed mucinous adenocarcinoma. Additionally, on imaging there was an enhancing pelvic lymph node concerning for metastatic spread. Tailgut cysts with malignant transformation to adenocarcinoma are rare and are typically treated surgically to obtain clear margins. However, neoadjuvant chemotherapy may be used in patients who have metastatic disease, which was pursued in the course of our patient’s care. This case presentation emphasizes the importance of a wide differential for presacral masses with atypical presentations raising concerns for underlying malignancy. Prompt recognition and intervention is imperative in cases of malignant transformation of tailgut cysts.